PENGEMBANGAN OBJEK WISATA BUDAYA : TAMAN PRASEJARAH LEANG-LEANG, MAROS, SULAWESI SELATAN - Mulyantari, Enny (Sekolah Tinggi Pariwisata AMPTA, 2018)
In the current era of globalization, the tourism sector has become one of the largest and strongest industries in the world, as well as the largest contributor to public and state revenues. Tourism has become part of the lives of people starting from the existing community in the city to the community in the village. Maros Regency in South Sulawesi has a lot of tourist attractions but the community has not been fully able to identify the tourism potential that exists in the region. This study aims to promote the potential, important values and strategies for the management and development of the Leang-leang Prehistoric Park as a tourist destination. The research result shows that Leang-Leang Prehistoric Park has a cultural tourist attraction containing commercial values that attract many tourists, with the assurance that the expenditure, time and cost,is worth for the experience obtained during the visit. Keywords: important value, tourist object, development, cultural heritage